Stroke: management and prevention. (September 2020) - Hadley, Gina; Gbinigie, Ivie I.; Buchan, Alastair M.
Abstract: Acute stroke treatment requires clear protocols to rapidly triage patients – using appropriate investigations – for endovascular thrombectomy and intravenous thrombolysis. Computed tomography (CT) excludes haemorrhage, CT angiography locates the occluded vessel, and perfusion magnetic resonance imaging identifies viable tissue. An organized approach to stroke care in a specialist environment reduces disability and saves lives. Adoption of a 'care bundle' approach including the active management of pyrexia and hyperglycaemia, and early screening for swallowing difficulties, is beneficial. Tailored secondary prevention, including assessment of the carotid arteries, is urgent as, for eligible patients, carotid endarterectomy should be done within 2 weeks. Anticoagulation in elderly individuals with atrial fibrillation is safer than is often assumed, and direct oral anticoagulants have changed the landscape of secondary prevention.